Literary Evidences of a Fivefold Structure in the Gospel of Matthew - Smith, Christopher R. (1997)
The current shift in emphasis in gospel studies from redaction criticism to literary criticism has called into question a longstanding belief about the structure of Matthew's gospel. Mark Allan Powell has described this shift and its effects succinctly in a recent article. Redaction criticism, he writes, has operated with premises which imply that ‘the changes an evangelist makes in the organization of source materials are especially significant for the determination of structure’. Redaction critics, therefore, having observed that ‘Matthew has added a large quantity of discourse material to what was taken over from Mark and has organized this material into five great blocks’, have favoured structural outlines that ‘organize the Gospel around these five prominent blocks of discourse’.1